Zinc Finger CCCH-Type Antiviral Protein 1 Restricts the Viral Replication by Positively Regulating Type I Interferon Response - Zhang, Baoge; Goraya, Mohsan Ullah; Chen, Na; Xu, Lifeng; Hong, Yan; Zhu, Meiyi; Chen, Ji-Long (Frontiers in Microbiology, 2020)
Zinc finger CCCH-type antiviral protein 1 (ZC3HAV1) is a host antiviral factor that inhibits the replication of specific viruses via mediating viral RNA degradation. In this study, we found that expression of ZC3HAV1 was significantly induced by infection with influenza A virus (IAV) and Sendai virus (Sev). It was shown that deficiency of IFNAR resulted in a dramatic decrease in the virus-induced expression of ZC3HAV1. Furthermore, transfection with poly (I:C) and treatment with interferon-β (IFN-β) induced the ZC3HAV1 expression. Interference with the endogenous expression of ZC3HAV1 enhanced the replication of influenza virus by impairing the production of IFN-β and MxA, following the infection of influenza virus. In contrast, ectopic expression of ZC3HAV1 significantly restricted the replication of influenza virus by increasing the IFN-β expression. In addition, ZC3HAV1 also promoted the induction of TNF and IL-6. These results suggest that ZC3HAV1 is induced by IFN-β/IFNAR signaling during IAV and Sev infection and involved in positive regulation of IFN-dependent innate antiviral response.